INOVASI PENGEMBANGAN ENTERPRISE RESOURCE PLANNING (ERP) DALAM MENINGKATKAN KINERJA PERUSAHAAN OTOMOTIF - Fasha, Andina; Yuwono, Wisnu; Ikhwanul Amri, Muhammad; Erika, Erika; Rosalina, Shelly; Kalia, Lee (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the implementation of Enterprise Resource Planning (ERP) systems in improving the performance of an automotive company in Indonesia. ERP plays a significant role in integrating business functions such as production, finance, human resources, and customer service, thereby enhancing the effectiveness of Supply Chain Management (SCM). This research uses a descriptive qualitative method based on secondary data from journals and official company sources. The results show that the implementation of SAP ECC 6.0-based ERP improves operational efficiency, decision-making accuracy, customer satisfaction, and inventory management. Key success factors include individual involvement, system quality, leadership support, and employee training. This study recommends continuous training and regular evaluation of the ERP system to maintain optimal performance.